Pengaruh Current Ratio & Debt to Equity Ratio Terhadap Harga Saham Perusahaan Manufaktur Sub-Sektor Makanan & Minuman - Hamzah, Hajrah (Universitas Negeri Makassar, 2025)
This study aims to examine the effects of the Current Ratio and Debt to Equity Ratio on stock prices within food and beverage companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. Using purposive sampling, 27 companies were selected for analysis. The data were analyzed using multiple regression and partial analysis to observe the impact of the Current Ratio and Debt to Equity Ratio on stock prices. Findings indicate that the Current Ratio and Debt to Equity Ratio together influence stock prices. The data analysis shows that 47% of stock price movements can be attributed to these two financial ratios, while the remaining 53% are affected by other factors. These results support the hypothesis that financial ratios like the Current Ratio and Debt to Equity Ratio provide valuable insights for investors regarding a company's financial stability. It is, therefore, suggested that investors also consider other elements, such as profitability and external market conditions, along with these financial factors when making investment decisions.